THE CORRELATION BETWEEN STUDENTS' ISLAMIC MORAL VALUES AND THEIR ENGLISH ACHIEVEMENT IN THE IMPLEMENTATION OF THE SCIENTIFIC APPROACH THROUGH ICT OF CURRICULUM 2013 AT JUNIOR IDGH SCHOOLS IN KAMPAR REGENCY OF RIAU PROVINCE - Abdullah Hasan (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
The main goal of this study is to find out the correlation between students' Islamic moral values and their English achievement in the implementation of the Scientific Approach Through ICT of Curriculum 2013 at Junior High Schools. The research utilizes a mixed method of quantitative and qualitative research with a quasi experimental study of pretest-postest non equivalent control group design. The sample of the study comprised 160 students and three Junior High schools in Kampar regency of Riau province. The schools are State Junior High School number 1 (SMPN 1) Bangkinang, Private Islamic Junior High School of Assalam (M.Ts As-Salam) and State Junior High School number 1 (SMPN 1) Kampar Timur. The scientific approach with three aspects of attitude, skill and krwwledge competencies through information Technology (ICT)and Islamic moral values are integrated in this study. Data are coUected using a test to measure the students' English achievement; then, observation and questionnaire are administered to investigate the students' Islamic moral values. Three research questions are proposed in this research The findings show significant relationship between English language achievement and Islamic moral values through the scientific approach through ICT of curriculum 2013. At last, the research finding hopefully able to become a model for English teaching instruction in Riau province locallly and in Indonesia nationally.